Women's Empowerment Through the Kembang Jayanti Program in Ganjar Sabar Village, Nagreg District, Bandung Regency - Siti Hasanah; Nandang Alamsah Deliarnoor; Neneng Yani Yuningsih (Khazanah Sosial, 2024)
This study aims to examine the pattern of women's empowerment through the Kube Kembang Jayanti Program by the Ganjar Sabar Village Government, Nagreg District, Bandung Regency. Ganjar Sabar Village as the focus of the research has quite complex women's problems where there are many cases of women, especially widows, who experience social, economic and religious problems. The Ganjar Sabar Village Government as a community service at the local level presents the Kube Kembang Jayanti Program to overcome this problem. This study uses a qualitative approach with a descriptive analysis model in describing the research results. The main data source in this study comes from the results of researchers' interviews with a number of parties involved both directly and indirectly in the Kube Kembang Jayanti Program. The results of this study show that the Ganjar Sabar Village Government has been quite successful in overcoming women's problems, especially widows, through the Kube Kembang Jayanti Program. This is based on the fulfillment of the three empowerment stage indicators which are the theoretical basis for this research. The three stage indicators are awareness, capacity building and empowerment. The Ganjar Sabar Village Government has been able to take a persuasive approach in the awareness stage, being able to provide facilities in the form of training programs, providing initial capital and also business tools for members of Kube Kembang Jayanti. Furthermore, Kube Kembang Jayanti members also receive sustainable benefits from the women's empowerment program by the Ganjar Sabar Village Government. However, at the empowerment stage, the Ganjar Sabar Village Government was not yet optimal in providing collaboration so that product marketing could be sustainable, this should be corrected so that the empowerment program can run optimally. The novelty in this study is that it attempts to research the women's empowerment program with a case study of the Kube Kembang Jayanti Program at the local level